Distributions of airflow in four rectangular section roadways with different supporting methods in underground coal mines. (February 2015) - Luo, Yonghao; Zhao, Yangsheng; Wang, Yi; Chi, Mingbo; Tang, Haibo; Wang, Shaoqing
Highlights: We have carried out an experimental campaign in a coal mine. Airflow distributions were investigated through statistical analyzes. The supporting methods influence the airflow velocity distribution. The low airflow velocity region increase with surface roughness. The risk assessment should be carried out in the low airflow velocity region. Abstract: A study has been carried out in four rectangular section roadways with different supporting methods in Yuwu Coal Company (a longwall mine), by measurements of airflow velocities in cross-section of the roadways. The asymmetrical distributions of airflow in each roadway section was obtained. The paper analyzes the low airflow velocity region of roadways through the drawing of the distributions of airflow in each roadway section. The supporting methods influence the low airflow velocity region around the roof and wall of roadways. It is shown that the low airflow velocity region increase with surface roughness of the roof and wall. The high airflow velocity region was located around the floor of the roadway with rough roof and wall. However, in the roadways with smooth roof and wall the high airflow velocity region was located around the center of section. The risk assessment should be carried out in the low airflow velocity region in the roadway with rough roof and wall. To ensure the safety of coal mining, higher volume of air intake or more smooth roof and wall of the roadways should be achieved in a dangerous zone.